Asgardia: Problematika dalam Pembangunan Peradaban Luar Angkasa - Larasati, Kandi Kirana; Ilmi, Amadda (CV Rewang Rencang, 2020)
Asgardia is an area that proves that the progress of human thinking is very visionary. It is an area in space that is called capable and will be a place to live for humans. The truth has not been fully proven, but efforts to regulate and implement it continues to be done. Because it has the support of various parties and communities that can be said to no longer want to live on earth. The way of recruitment is also unique, the Asgardia team has established an official website for registration to become prospective citizens in the region, the number is not small. However, it remains a concern for many to explore whether it is a hallucination or a reality. Meanwhile, regional consensus conferences are also underway, which can be witnessed and immortalized in videos uploaded via YouTube. They have also determined a kind of national emblem to the form of government, but the official status of